TINJAUAN HUKUM TERHADAP PUTUSAN HAKIM DALAM PERKARA TINDAK PIDANA PENCURIAN YANG DILAKUKAN OLEH ANAK - Nopiana Mozin (PT. Jurnal Center Indonesia Publisher, 2024)
For the sake of realizing a prosperous, just and prosperous Indonesian society based on Pancasila and the 1945 Constitution. The quality of Indonesia's human resources must be continuously improved for national development capital and making Indonesia a developed country. It also includes attention to youth and children as the next generation, so that one day they can bring Indonesia into a developed country. Talking about the problem of adolescents and children is an interesting subject to be discussed and discussed hotly these years of years the level of juvenile delinquency in narcotics abuse, brawl that leads to criminal acts, more specifically criminal acts of theft perpetrated by children. In the current era, we hear a lot of theft, both adults and young children. According to article 1 number 1 of the Child Protection Act,